(E)-2-{[1-Carboxy-2-(1H-indol-3-yl)ethyliminio]methyl}-6-hydroxyphenolate - Ba-Salamah, Salah Ahmed (International Union of Crystallography, 2011)
In the zwitterionic title compound, C(18)H(16)N(2)O(4), the dihedral angle between the planes of the benzene and indole rings is 26.38 (10)°. An intramolecular N—H⋯O hydrogen bond generates an S(6) ring motif. In the crystal, molecules are linked through N—H⋯O, O—H⋯O and C—H⋯O hydrogen bonds into infinite chains propagating in [010].